Efek Moderasi Moralitas Individu terhadap Hubungan Pengendalian Internal dan Kecendrungan Kecurangan - Dewi Nidia Soepriadi; Theophilia Fina Leiwakabessy (Penerbit Goodwood, 2023)
Purpose: The aim of this research is to examine the moderating effect of individual morality on the relationship between internal control system and the tendency of village financial management fraudulency Methodology/approach: The sampling method was purposive sampling with a total sample of 51 respondents from 20 villages in Ambon City. The data collection technique used was a survey technique using questionnaires. Data analysis used moderated regression analysis Results/findings: The results of the study explained that the internal control system has a negative effect on the tendency of fraudulence and individual morality, which acts as a moderating variable that strengthens the relationship between the internal control system and the tendency of village financial management fraudulency. Limitations: The results of this study indicate that the independent variables internal control system and individual morality as moderating variables only affect the tendency of fraud in village financial management by 30.9%, meaning more than 69.1% are influenced by other factors outside the model. Other factors can be in the form of competence of village officials, as well as compliance with regulations and other behavioral factors that can contribute to the tendency of village financial management fraudulency. Contribution: For the government traditional villages in Ambon City to make the role of state saniri more effective which carries out the supervisory function as the implementation of the internal control function to prevent the occurrence of village financial management that is not in accordance with the rules and can lead to fraud. Novelty: This research was conducted in a village in Ambon City which has the status of a traditional village whose village government system upholds local customs and wisdom so that it is different from other villages based on administrative area.